Efficacy and Safety of the 64Cu(II)Cl2 PET/CT for Urological Malignancies: Phase IIa Clinical Study. (21st June 2021) - Mascia, Manlio; Villano, Carlo; De Francesco, Valerio; Schips, Luigi; Marchioni, Michele; Cindolo, Luca
Abstract : Purpose of the Report: The aim of this study was to evaluate safety and efficacy of copper-64(II)dichloride ( 64 Cu(II)Cl2 ) as a new PET tracer for urological malignancies (UMs). Methods: Patients with UM were enrolled in a prospective study. All patients were staged with preoperative CT and 64 Cu(II)Cl2 PET/CT. Patient characteristics, anatomical and functional imaging, and final histopathology were recorded. Surgical specimens for histopathological examination were collected. To determine time-activity curves for 64 Cu(II)Cl2 uptake in UM and normal tissues, SUVs were calculated. The safety of 64 Cu(II)Cl2 was assessed. Results: Twenty-three patients were included. An administered activity of 174.7 MBq (4.72 mCi) for 64 Cu(II)Cl2 was equal to 9.80 mSv of the effective dose. The median SUVmax values were 5.7, 0.9, 1.8, and 9.8 for the prostate, bladder, penis, and kidney, respectively. Median SUVmax values were higher in organs with a malignancy in comparison with healthy tissue (prostate [11.5 vs 5.3, P < 0.001], bladder [6.2 vs 0.9, P = 0.007], and penis [3.9 vs 1.3, P = 0.027]), but not in the kidneys (5.0 vs 10.4, P = 0.998). The highest area under the curve (AUC) was reported for prostate cancer (AUC, 0.978), and the lowest for penile cancer (AUC, 0.775). The detection rates based on the best suggested cutoff according to the SUVmax were 85.7% (6/7) for prostate and bladder and 83.3% (5/6) for penile cancer. Neither drug-related effects nor physiologic responses occurred, nor adverse reactions. Conclusions: 64 Cu(II)Cl2 is an effective and well-tolerated tracer in patients with UM. Our results show higher SUVmax in cancer patients than in healthy subjects. Our findings suggest that 64 Cu(II)Cl2 PET/CT is useful in patients affected by prostate, bladder, and penis cancer.